Epidemiology of injuries in United States high school track and field. 2008-2009 through 2013-2014 - Pierpoint, L. A.; Williams, C. M.; Fields, S. K.; Comstock, R. D. (The American Journal of Sports Medicine, 2016)
Background: Track and field is one of the most popular high school sports among boys and girls, but epidemiological research on the sport and its individual events has been limited. Purpose: To describe injury rates and patterns in boys` and girls` high school track and field. Study Design: Descriptive epidemiology study. Methods: A retrospective epidemiological analysis of injury and exposure data from a longitudinal national high school sports injury surveillance system was conducted. Results: From 2008-2009 through 2013-2014, 2485 track and field injuries occurred during 2,962,308 athlete exposures (0.84 injuries per 1000 athlete exposures). Injury rates were higher in competition versus practice for both sexes. Girls had higher injury rates than boys overall (rate ratio, 1.37; 95% CI, 1.27-1.48) and in practice (rate ratio, 1.60; 95% CI, 1.46-1.76), but competition injury rates did not differ. Overuse/chronic injuries accounted for 27.5% and 36.2% of boys` and girls` track and field injuries, respectively. The majority of injuries were to the lower extremity. Sprints, distance running, and jumps accounted for over 65% of all track injuries. Boys sustained a greater proportion of injuries in relay events (injury proportion ratio, 2.02; 95% CI, 1.69-2.36) but fewer in hurdle events (injury proportion ratio, 0.51; 95% CI, 0.23-0.78). Conclusion: Injury rates varied by event, sex, and competition versus practice exposure. To increase effectiveness, targeted strategies for injury prevention should be driven by an understanding of such differences. Because many track and field injuries are overuse/chronic across sexes and for both competitions and practices, coaches and athletic trainers should be adept at recognizing early injury symptoms, intervene to treat minor injuries in order to prevent severe injuries, and ensure the prompt diagnosis and management of all injuries.